Analisis Implementasi Kebijakan Fast-Track Pada Jenjang Sarjana-Magister Pendidikan Agama Islam - Hapsari, Aprilia Putri (AKSI: Jurnal Manajemen Pendidikan Islam, 2024)
The existence of a fast track program policy is intended to facilitate students who have superior academic qualities so that they can continue their studies in a relatively short time and offer efficient financing because this program carries an accelerated concentration. Currently, one of the faculties and study programs implementing a fast- track program at the bachelor-master level is the Faculty of Islamic Religion, Islamic Religious Education Master's Study Program, UAD. The researchers were then interested in analyzing the implementation of the fast track policy in these locations. Apart from that, researchers also tried to analyze the impact of implementing the fast track program at the bachelor-master level in Islamic Religious Education. This research is a type of descriptive-analytic research with a qualitative approach to presenting research data. Data was obtained through data collection techniques in the form of document reviews, observations, and interviews with related sources. The results of this research describe the program implementation process from the selection stage to the implementation of lectures and final assignment assistance facilities. Apart from that, this research also reveals positive and negative impacts that affect the faculty/study program organizers, students, and the field of Islamic education in general.